ANALISIS PENGARUH FUNDAMENTAL PERUSAHAAN TERHADAP RISIKO SISTEMATIS SAHAM PADA PERUSAHAAN-PERUSAHAAN PROPERTI - Slamet Herutono (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2009)
Fundamental factor is one of necessary factor used by investors to make investment decission in the capital market. This study investigated the impact of fundamental factor of company on systematic risk (beta) stock. The data used in this research are the data of financial statement and stock price, obtain from Indonesian Capital Market Directory (ICMD) 2004-2006. The sample comprised 28 pooled companies from property industry listed on the Bursa Efek Indonsia (BEI) for the period of 2004 - 2006. The company variables are current asset to total asset, debt to equity ratio, return on equity, earning per share, and financial leverage. The statistical method used in this reasearch is multiple linear regression with panel data. The result found that current asset to total asset, debt to equity ratio, return on equity, earning pershare, and financial leverage simultaneously have significant effect on beta stock. But only current asset to total asset, return on equity, earning pershare, and financial leverage individually have significant effect on beta stock. Overall of independent variables could explain about 49.08 percent beta stock variation and the rest explained by other variables about 50.02 percent. It means that the fundamental factor of company is not only factor that influenced beta stock in the BEI.Keywords: fundamental factor, beta stock, panel data